Hoarding: Obsessive Symptom or Syndrome? - Sansone, Randy A. (Matrix Medical Communications, 2010)
Through media depictions, the public is becoming increasingly aware of the phenomenon of hoarding. Hoarding refers to the excessive acquisition of relatively worthless items, which eventually results in the compromise of living space and/or the daily activities of affected individuals. As a symptom, hoarding is relatively common in a significant minority of individuals with obsessive-compulsive disorder. In the context of obsessive-compulsive disorder, symptoms typically emerge in the teens through the early 20s. However, hoarding also appears to exist as a distinct syndrome, which is characterized by late onset, childhood adversity, various Axis II traits, and a history of alcohol misuse. While the explicit position of hoarding in the psychiatric nomenclature remains undetermined, this behavior is likely to surface in both psychiatric and primary care settings.